A Molecular Line Survey around Orion at Low Frequencies with the MWA - Tremblay, C.; Jones, P.; Cunningham, M.; Hurley-Walker, Natasha; Jordan, Christopher; Tingay, Steven (Institute of Physics Publishing, 2018)
The low-frequency sky may reveal some of the secrets yet to be discovered. Until recently, molecules had never been detected within interstellar clouds at frequencies below 700 MHz. Following the pilot survey toward the Galactic center at 103-133 MHz with the Murchison Widefield Array, we surveyed 400 deg2centered on the Orion KL nebula from 99 to 170 MHz. Orion is a nearby region of active star formation and known to be a chemically rich environment. In this paper, we present tentative detections of nitric oxide and its isotopologues, singularly deuterated formic acid, molecular oxygen, and several unidentified transitions. The three identified molecules are particularly interesting, as laboratory experiments have suggested that these molecules are precursors to the formation of amines.